NEED ANALYSIS OF ENGLISH LEARNING DIGITAL MEDIA FOR JUNIOR HIGH SCHOOL STUDENTS - Nurul Afiyattena; Nadilla Dwi Haerani (Cirebon International Conference on Education and Economics Proceeding, 2024)
The digital media are now widely spread in educational fields, unfortunately the use of digital learning media was not fully implemented in rural schools, almost several schools in rural areas are not accessible to the widespread and rapid development of digital media in learning, especially digital media for English learning. Investigating students’ need in regard with the digital media for learning English is the purpose of this research. Mix Method (Quantitative and qualitative design) was used to dig students’ need. This study included one English teacher as an informant in addition to thirty-two students of the eight grade of junior high school who were purposefully recruited as participants. Through interviews, FGD, and questionnaires, the data were acquired. The results showed there were (48,1 %) students were inadequate interest in learning English due to lack of learning media (62,1 %), in regard with students’ need, (55,6 %) students need of digital learning media that used combination of semiotic resources such audio, visual, and linguistics. in regard with the English skills and English learning topic it’s about (50,7 %) students need of English vocabulary, and for the English topic, they need short dialogue like introduction (44,4%) which supported by the use digital video animation which get (57,3 %), for the last need most of the students (63,2) % were motivated to have the opportunity to learn English using Digital learning media.